Disease-specific knowledge and information preferences of young patients with congenital heart disease. (29th April 2013) - Lesch, Wiebke; Specht, Katharina; Lux, Anke; Frey, Michael; Utens, Elisabeth; Bauer, Ulrike
Abstract: Aims: Persons suffering from congenital heart defects require lifelong specialist medical care. Failure to attend cardiological follow-up examinations and risky health behaviour in the transition phase may cause severe medical complications. A good level of disease-specific knowledge enhances compliance. Therefore, the study's aim was to investigate: (a) the level of disease-specific knowledge, (b) information preferences, and (c) sources of information for children, adolescents, and young adults regarding their illness. Methods and results: In all, 596 patients, aged 10–30 years, participated in this cross-sectional survey study (response rate: 53%). All patients were already enrolled in the German National Register for Congenital Heart Defects. The main outcome measures included disease-specific knowledge, information preferences, and information sources regarding patients' individual cardiac condition. The patients demonstrated a major knowledge gap concerning their illness and how to live with it. For all three age groups, patients' information needs were unmet on nearly half of the topics of interest. Children's information needs were comparable to those of adolescents and adults concerning several important topics, for example, work/career, sports. Information preferences varied according to age and gender, rather than disease severity. The most important sources of information were physicians (71.0%), family and friends (58.2%), and the Internet (37.5%). Conclusion: The study revealed substantial knowledge gaps, indicating a need for structured multidisciplinary patient education interventions. These interventions should start as early as in childhood and help patients manage their condition and assume responsibility for their own health, so that the transition phase runs smoothly.